Comparison of sunlight-driven photocatalytic activity of semiconductor metal oxides of tin oxide and cadmium oxide nanoparticles - Vidhya, M.; Raja Pandi, P.; Archana, R.; Sadayandi, K.; Sagadevan, Suresh; Gunasekaran, S.; Podder, Jiban; Mohammad, Faruq; Al-Lohedan, Hamad A.; Oh, Won Chun (Elsevier, 2020)
This study is aimed to investigate the photocatalytic efficiencies of two different metal oxide nanoparticles (NPs), SnO2 and CdO formed by the simple chemical precipitation route. The synthesized metal oxide NPs were examined by several techniques in order to understand the morphological (FESEM), structural (XRD), functional (FTIR), and optical (UV-vis) characteristics. The analysis of results confirmed the successful formation of SnO2 and CdO NPs along with their desired chemical compositions and electronic band structures. Further testing of their photocatalytic efficiency with the use of methylene blue (MB) degradation in the presence of sunlight confirmed their catalytic efficiency. Within the two NPs, the SnO2 has a little higher activity as compared to the CdO NPs and this can be attributed to the increased surface area by means of the formation of nanospheres for the SnO2 ones, while the rod-shaped agglomerated structure with less surface area delaying the rate of degradation. Further from the analysis, it can be confirmed for the superior photocatalytic activity of SnO2 particles having spherical shape against the rod-shaped CdO NPs. © 2020 Elsevier GmbH